CSR na Mazowszu – wymiar instytucjonalny - Jastrzębska, Ewa (Studia KPZK, 2017)
CSR on Mazovia – Institutional Dimension. Corporate social responsibility (CSR) is defined as the responsibility of enterprises for their impacts on society. For the effective implementation of this concept are very important institutions, understood as a permanent (legal, organizational and customary) determinants of repetitive human behaviour and peopleto- people interaction. Institutions can therefore be both organisations that promotes this concept and CSR projects or strategies. The aim of the article is to review the thesis that the Mazovia is the driving force of the development of CSR in Poland, carried out on the basis of desk and web research. By evaluating the degree of institutionalisation of CSR in Mazovia, based on an analysis of the activities of the various sectors in this field, it was found that most activities for the implementation of this concept is undertaken in Mazovia, and many of them have coverage nationwide.
Keywords: business; corporate social responsibility; CSR; institutions; Mazovia; organisations; public administration